Cellular and Molecular Mechanism of Cell Proliferation in Human Gastric Cancer Drug-Resistant Cells After Hyperthermia and Cisplatin: Role of mRNAs and Long-Non-coding RNAs - Zadeh, Firoozeh Abolhasani; AkbariRad, Mina; Lian, HuoJun; Wei, Ying; Yang, Jing; Feng, Xiaoke; Akhavan-Sigari, Reza (Turkish Journal of Gastroenterology, 2022)
Background: Since thermo-chemotherapy was suggested as an effective treatment for gastric cancer, we aimed to evaluate the effects of hyperthermia combined with cisplatin (DDP) on the inhibition of human gastric cancer drug-resistant cells in vitro and explore its possible mechanisms. Methods: SGC-7901/DDP cells were cultured and divided into control, cisplatin, hyperthermia, and hyperthermia combined with cispla- tin groups. Hyperthermia was done at 42°C, 44°C, 46°C, 48°C, and 50°C for 12 h, 24 h, 36 h; 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl- 2H-tetrazolium bromide (MTT) assay detected the proliferation of SGC-7901/DDP at different time and temperature, and the apoptotic rate of SGC-7901/DDP cells was evaluated by using Annexin staining assay. High-throughput Chromatin immunoprecipitation (ChIP)- seq was applied to test long non-coding RNA expression in SGC-7901/DDP cells. Then, real-time fluorescence quantitative polymerase chain reaction was used to verify the expression of long non-coding RNA in all groups. Results: Double staining showed that hyperthermia combined with cisplatin increased the rate of early apoptosis of SGC-7901/DDP cells. Long non-coding RNA high-throughput ChIP-seq showed a significantly larger amount of long non-coding RNAs and mRNAs in the cells treated with hyperthermia combined cisplatin group in comparison with the control group. We observed that the upregulated mRNAs and long non-coding RNAs were highly related to immune system response and CD95 signaling pathway in nucleus, and down- regulated mRNAs and long non-coding RNA were highly related to Mammalian target of rapamycin (mTOR) and Tumor necrosis factor (TNF) receptor signaling pathway in cytoplasm. Conclusion: Hyperthermia combined with cisplatin reversed the expression of a large number of mRNAs and long non-coding RNAs in human gastric cancer drug-resistant cells. The molecular mechanism of inhibiting the proliferation of human gastric cancer drug- resistant cells may be related to the upregulation of long non-coding RNAs and mRNAs contributed in CD95, mTOR, and TNF receptor signaling pathway. Cite this article as: Abolhasani Zadeh F, Akbarirad M, Lian H, et al. Cellular and molecular mechanism of cell proliferation in human gastric cancer drug-resistant cells after hyperthermia and cisplatin: Role of mRNAs and long-non-coding RNAs. Turk J Gastroenterol. 2022;33(5):377-386.